Prevalence and impact of disability in women who had recently given birth in the UK - Šumilo Dana; Kurinczuk Jennifer J; Redshaw Maggie E; Gray Ron (BMC, 2012)
Abstract Background Maternity services should take into account the needs of all women, including those related to disability. No reliable information, however, exists on the extent and characteristics of disability in this population in the UK. This brief report provides an overview of the prevalence of disability in women giving birth in the UK as measured by the presence of a limiting longstanding illness (LLI). The demographic, socio-economic, lifestyle and pregnancy related characteristics and child health outcomes are summarised to inform maternity and postnatal care service planning, and policy development. Methods Secondary analysis of data on 18,231 mother-child pairs from the nationally representative UK Millennium Cohort Study. The baseline interviews with families were carried out in 2001-2002. The LLI prevalence in women who had recently delivered was estimated, and relevant characteristics and differences in outcomes compared using descriptive statistics taking into account the study design and non-response. Results 9.4% (95% CI 8.7-10.0) of women who had recently given birth reported having an LLI. Musculoskeletal, respiratory and mental disorders accounted for most of the health problems. A significantly higher proportion of women with an LLI received means-tested financial benefits, had no educational qualifications and suffered from intimate partner violence compared to women who did not have an LLI (49.3% vs 35.3%, 20.4% vs 15.0%, 6.0% vs 3.3%, respectively). They were also more likely to smoke throughout pregnancy than women without an LLI (29.2% vs 20.8%), have a preterm birth (10.9% vs 6.8%) and be lone parents (19.5% vs 13.9%). Only 25.6% of children of mothers with an LLI were breastfed for more than three months compared to 33.4% of infants of mothers who did not have an LLI. At the age of seven years, 12.0% of children of mothers with an LLI had an activity limiting health problem themselves compared to 6.2% of children of mothers without an LLI. Conclusions Disability in women who had recently delivered is relatively common. It is associated with social and economic inequalities and worse pregnancy and child related outcomes. Apart from condition-specific support during and after pregnancy, disabled women may require extra help from health professionals to quit smoking, continue breastfeeding, and reduce intimate partner violence.